Indirect study of the 3He(n, p)3H reaction at cosmological energies. (October 2020) - Spampinato, C.; Pizzone, R.G.; Spart`a, R.; Couder, M.; Tan, W.; Burian, V.; Chae, K.Y.; D'Agata, G.; Guardo, G.L.; La Cognata, M.; Lamia, L.; Lattuada, D.; et al.
Abstract: In the network of reactions present in the Big Bang nucleosynthesis, the 3 He(n, p) 3 H reaction has an important role which impacts the final 7 Li abundance. The Trojan Horse Method (THM) has been applied to the 3 He(d, pt)H reaction in order to extract the astrophysical S(E)-factor of the 3 He(n, p) 3 H reaction in the Gamow energy range. The experiment will be described in the present work together with the first preliminary results.